(untitled) (Journal for Studies in Humanities and Social Sciences, 2019)
This essay is a pragmatic study of the roles that referential elements play in the titles of church print posters in Nigeria. Perhaps it is unarguable that church print posters are meant to persuade the audience to fall in line with the ideology that the posters represent. What is probably not clear is the modus operandi of the interplay between the linguistic items deployed in those posters and the human cognitive system. This essay therefore describes the roles that linguistic items, particularly referentials, play in the persuasiveness of church posters. It is against this background that this paper establishes that referential elements aid persuasion by reducing processing cost in the utterance computation process and making the mental representation of objects in the physical world easily accessible. In doing this, the researchers collected fifty posters from selected churches that have national outlook and strong media outlets. In other to make our analysis more explicit, the researchers deployed Wilson and Sperber’s Computation Heuristics. This study therefore concludes that reference elements (definite noun phrase and indefinite noun phrase) create accessibility of mental concepts at the explicit level which automatically translates to less processing effort, and this has a persuasive effect at the implicit level on the reader of the church posters.